Evolution of Filament Formation in Ni/HfO2/SiOx/Si‐Based RRAM Devices. (9th October 2015) - Wu, Xing; Mei, Sen; Bosman, Michel; Raghavan, Nagarajan; Zhang, Xixiang; Cha, Dongkyu; Li, Kun; Pey, Kin Leong
Abstract : The evolution of metal nanofilaments formed in dielectric layers of Ni/HfO2 /SiO x /n + Si stacks and the role of Ni atoms during SET (low resistance) and RESET (high resistance) are quantitatively studied. The shape of the filaments is confirmed as conical with a broader distribution in HfO2 after a positive switching voltage is applied to the Ni electrode during SET. Residual Ni atoms are detected in the dielectric layers after RESET.